Association between organic cation transporter genetic polymorphisms and metformin response and intolerance in T2DM individuals: a systematic review and meta-analysis - Peng, Aiyu; Gong, Chunmei; Xu, Yuanfei; Liang, Xiongshun; Chen, Xiaoping; Hong, Wenxu; Yan, Junxia (Frontiers in Public Health, 2023)
Background Variants in Organic cation transporter (OCT) genes play a curial role in metformin pharmacokinetic and are critical for diabetes treatment. However, studies investigating the effect of OCT gene polymorphisms on metformin response have reported inconsistent results. This review and meta-analysis aims to evaluate the associations of OCTs gene polymorphisms with metformin response and intolerance in type 2 diabetes mellitus (T2DM). Method A systematic search was conducted on PubMed, EMBASE, CNKI, WANFANG DATA and VIP database for identifying potential studies up to 10 November 2022. The Q-Genie tool was utilized to evaluate the quality of included studies. Pooled odds ratios (OR) or standardized mean differences (SMD) and 95% confidence intervals (95% CI) were calculated to determine the associations between OCTs genetic polymorphisms and metformin response and intolerance that reflected by glycemic response indexes, such as glycated hemoglobin level (HbA1c%) or change in glycated hemoglobin level (ΔHbA1c%), fasting plasma level (FPG) or change in fasting plasma glucose level (ΔFPG), effectiveness rate of metformin treatment, and rate of metformin intolerance. For the variants identified just in one study or can’t perform pooling analysis, a qualitative review was performed. Results Thirty related eligible studies about OCTs genes (SLC22A1, SLC22A2 and SLC22A3) and metformin pharmacogenetic were identified. Fourteen, three and six single nucleotide polymorphisms (SNPs) in SLC22A1, SLC22A2 and SLC22A3 respectively were investigated. Meta-analysis indicated that the SLC22A1 rs622342 polymorphism is associated with HbA1c reduction (AA vs AC: SMD [95% CI] = -0.45 [-0.73--0.18], p = 0.001). The GG genotype of the SLC22A1 rs628031 polymorphism is associated with a more favorable effect on fasting plasma glucose (FPG) reduction (GG vs AA: SMD [95 %CI] = -0.60 [-1.04--0.16], p= 0.007; GG vs AG: -0.45 [-0.67--0.20], p <0.001). No statistical association was found between the remaining variants and metformin response and intolerance. Conclusion SLC22A1 rs622342 and rs628031 polymorphisms were potentially associated with glycemic response to metformin. These evidences may provide novel insight into gene-oriented personalized medicine for diabetes.